Functional Composite Materials
Being both strong and lightweight, composite materials have already found wide-ranging uses in structural and engineering contexts. Through advancements in materials science and engineering the potential for further applications of composite materials can be achieved by introducing functionality. Functional Composite Materials focuses on this exciting new generation of materials. Sitting at the intersection of physics, chemistry, materials science and engineering, we welcome contributions on all types of composite materials — the only caveat is that composite functionality must be clearly demonstrated.